Hidden Mutations in Cornelia de Lange Syndrome Limitations of Sanger Sequencing in Molecular Diagnostics. Issue 1 (2nd December 2014) - Braunholz, Diana; Obieglo, Carolin; Parenti, Ilaria; Pozojevic, Jelena; Eckhold, Juliane; Reiz, Benedikt; Brænne, Ingrid; Wendt, Kerstin S.; Watrin, Erwan; Vodopiutz, Julia; Rieder, Harald; Gillessen‐Kaesbach, Gabriele; et al.
<x xml:space="preserve">Abstract</x> High‐coverage gene panel sequencing using buccal mucosa DNA samples of patients with Cornelia de Lange Syndrome could identify de‐novo mutations in NIPBL that were not detected by conventional Sanger sequencing approaches. The figure compares the electropherograms of Sanger sequencing analyses on blood, buccal mucosa and fibroblasts DNA samples of all three patients. While none of the mutations was identified in blood and buccal mucosa samples all mutations were detected in DNA of the fibroblast samples. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>